2000
DOI: 10.1176/appi.ajp.157.3.460
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Cognitive Impairment at Long-Term Follow-Up in Adolescents Treated With ECT for Severe Mood Disorder

Abstract: The results suggest that adolescents given ECT for severe mood disorder do not suffer measurable cognitive impairment at long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(55 citation statements)
references
References 5 publications
2
48
0
5
Order By: Relevance
“…These results support other long-term studies that have found no cognitive differences at follow-up (Cohen et al 2000;Russell et al 2003). When we analyzed the results with a repeated-measures method, no significant interaction time · group was found.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results support other long-term studies that have found no cognitive differences at follow-up (Cohen et al 2000;Russell et al 2003). When we analyzed the results with a repeated-measures method, no significant interaction time · group was found.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, our study supports the research of Cohen et al (2000) with affective patients. Theirs was the only long-term follow-up study conducted with a sample of adolescent patients treated with ECT, and they found no differences in neuropsychological variables between the ECT group and a psychiatric comparison group.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Generally a decline in processing speed reported during ECT (58), but not decline in IQ. Cognitive functions are known to recover once ECT is completed and the recovery appears to be irrespective of the age of the patient (75). A recent review by the Food Drug Administration (FDA) found that cognitive function recovery following ECT may take up to six months after the completion of ECT (76).…”
Section: Discussionmentioning
confidence: 99%